STATUS OF MUI’S RECOMMENDATION IN FACING ISLAMIC CONTEMPORARY ISSUES IN INDONESIA - Fatimah Zuhrah; Ardiansyah Ardiansyah; Amar Adly (State Islamic University of North Sumatra Indonesia, 2020)
The research formulates the problem of how the position of the MUI’s recommendation in the legal system, the position of the MUI in the Muslim community and the MUI’s recommendation answers to the contemporary problems of Muslims in Indonesia. This study uses qualitative methods for data collection techniques, analysis and reports. The research findings show that in the legal system in Indonesia the MUI’s recommendation does not meet the elements as a statutory regulation. Where, the MUI’s recommendation is not generally binding and is not made by an institution authorized to stipulate laws and regulations, so that the MUI’s recommendation does not have binding legal force, has no legal sanctions, is an appeal and information, and as a legal reference for the Muslim community, MUI’s recommendation and The MPU differs from its enactment. Other findings show that for the Muslim community in Indonesia the position of the MUI’s recommendation is very urgent and important because it is the foundation of the religious community and the MUI’s recommendation is seen as knowledge that can educate the community. So that the MUI’s recommendation is seen as being able to answer and be a solution for all contemporary problems of Muslims in Indonesia. Keywords: Recommendation of MUI, Contemporary problem, Islamic Society in Indonesia.